EXPECTANCY VIOLATION THEORY (EVT) DALAM FILM ‘DI TIMUR MATAHARI’ (Analisis Peran Vina, Gadis ‘Cina’ Bersuamikan Papua) - agustina, dwi pela (SOURCE : Jurnal Ilmu Komunikasi, 2018)
Intercultural is the self most effective inter-personal between two people who are of differentcultural backgrounds. The Expectancy Violation Theory (EVT) is a theory that explains thatpeople have expectations about nonverbal behavior of others. Unexpected changes that occurwithin a conversation between communicators can cause a feeling of discomfort or even angerand often ambiguous. Similarly, in the film, the film-makers and actors make the dialogue alongwith the non-verbal language in a movie for menyeampaikan his message to the audience. Inthis case, the authors raised the film "Di Timur Matahari" as its object, where there is a lot ofexpectation violation in the interaction of players in the film. Therefore, of course, there wasmuch suspicion in the prediction and the communication interaction. Both predictions andexpectations created by his players, as well as predictions that are owned by the audiencewatching the film. Both the positive and negative violations.Keywords : Communication, Intercultural, Verbal, Non-Verbal, Expectancy Violation,Prediction, Film